Manejo e potencial socioeconômico dos produtos florestais não madeireiros na Reserva de Desenvolvimento Sustentável do Uatumã, Amazonas - Giatti, Otavio (Instituto Nacional de Pesquisas da Amazônia - INPA, 2019)
Gathering of non-timber forest products (NTFPs) carried out by traditional communities is an important strategy for the conservation of agrobiodiversity and the production of food, structures and medicines for the subsistence and income generation of these families. Therefore, the present research had the objective of evaluating the socioeconomic and environmental potential of NTFPs as a sustainable economic activity for the Uatumã Sustainable Development Reserve (RDS) family units in Amazonas. For this, the data were collected through semi-structured interviews with 23 family units of six communities, working with NTFPs in the Uatumã RDS with eight product resellers marketed by the families, in order to understand the factors that involve the production of these products: that is, the abundance of taxa; the interests of traditional populations; practices of use, management; the cost of production; productivity; the profitability of work; and the perception of the residents about the potentiality of the different products. Twenty-four non-timber forest products collected in four environments were evaluated: forest managed; igapó; sítio and capoeira, being the forest managed, the environment with greater co-occurrence of NTFPs. The products are used for food, manufacturing and medical purposes, being the food products with the greatest diversity. Among these, the fruits of açaí, bacaba, patauá, piquiá, uchi-coroa, uchi-liso and tucumã presented the maturation period corresponding to the frequency of collection. Among the nine most collected products, six are for food purposes. It was also found that 16 products were commercialized by at least one family. Of these, only six products were commercialized by more than three families, being: Amazonian nut seeds, tucumã fruits, resin of dark breu; handicrafts of vines and tucumã leaf; oils of copaíba and andiroba. The cost of labor was the one that most influenced the cost of production of all products. The supply and demand system has influenced the value chain of all products. Breu was the product that best compensated the producing families, followed by tucumã, Amazonian nut, copaíba and andiroba (it was not possible to calculate the profitability of vines). However, breu and vines present low demand, which makes constant commercialization impossible. Amazonian nut and tucumã, in general lines, present seasonality of production, which restricts commercialization in a few months. The andiroba besides having seasonal production and the oil being manufactured in a handcrafted way does not allow great production, and despite having greater demand than supply has the market price stagnated. Copaíba presents production throughout the year, it is not perishable and has demand greater than supply, but the market price remains stagnant. Among the commercialized NTFPs, copaiba was the product best evaluated by households. In view of the results presented, it is concluded that NPFs are sources of inputs that mainly contribute to household food security. Regarding the management of the most commercialized NFPs, the need to intensify the management of mainly copaíba oil was highlighted. Regarding the potential of the PFNM value chain, it is concluded that breu, copaíba and tucumã presented higher potential compared to Amazonian nut, vines and andiroba. Finally, all the products presented socioeconomic potential, but there is a need for the involvement of the deliberative board, neighborhood association and city halls for the construction of a strategic planning according to the results presented in this research
Keywords: manejo de recursos naturais